PERANCANGAN PAMFLET DALAM BENTUK MEDIA CETAK DI MTs KOTO ANAU, KABUPATEN SOLOK - Yasfa Ilhami; Budiwirman .; Lisa Widiarti (DEKAVE : Jurnal Desain Komunikasi Visual, 2012)
Abstrack Purpose of this study is to (1) promote Mts Koto Anau to the people who are in or outside Koto Anau, (2) designing pamphlet that both visually and verbally and (3) create a design that is different from pre-existing design with its own characteristic. data were collected by two methods, namely primary and secondary data collection of interviews and obsevartion, while the secondary data collection can be obtained from internet or other data. In making this final work, metide used SWOT analysis which is contained within Strenghts, Weaknesses, Opportunities and Threat that could produce a work that can convey the message in the pamphlet. Keywords: promosi, pamflet, perancangan.